The influence of the CSR Committee in firms’ financial and non-financial performance: evidence from France, Germany, and the UK - Lopes, A.I.; Jorge, I. (European Accounting Association (EAA) Virtual Congress 2021, 2021)
The CSR committee is a corporate governance mechanism used by companies to promote and develop corporate social responsibility. It must promote a CSR oriented strategy, include it in the company’s policies and monitor the compliance with those said policies. This study is an analysis of how a CSR committee can influence firms’ performance. The sample consists of 415 companies from the top 3 countries with the biggest economies in the European Union. In the first approach, it will be analysed solely the influence of the CSR committee on performance. Secondly, it will be analysed the influence of a CSR committee in an environmentally sensitive industry, and finally, the influence of the implementation of the Directive 2014/95/EU in firms with a CSR committee. The results show that the existence of a CSR committee is generally positively associated with performance by the company. No generalized relationship was found between the fact that a company has a CSR committee and belongs to an environmentally sensitive industry, and its performance. Regarding the implementation of the Directive 2014/95/EU, in the sample considered, its effect was also not relevant for the companies’ performance.